PENERAPAN METODE KERJA KELOMPOK DALAM PENGEMBANGAN DIRI DI BIDANG TARI DI SMA NEGERI I LUBUK ALUNG - Novila Hesti; Susmiarti Susmiarti; Darmawati Darmawati (FBS Universitas Negeri Padang, 2013)
Abstract The research armed at describing the implementation of group work model in the self development during the dance activity of SMA N 1 Lubuk Alung. The design of the research was qualitative using descriptive method. The instrument of the research was the researcher. The methods used were field observation. The data was collected through observation, interview, library research and the field note the students’ activities. The data was analyzed the described. From the research, it was concluded that the implementation of group work method found to be advantageous and improved students learning outcome during the activity of self-development in the dance class at SMA N 1 Lubuk Alung.